Evaluation of solvents efficiency in condensate banking removal (2009)
This work describes experimental design and tests performed to simulate gas condensate reservoir conditions below dew point in the laboratory using three different compositions of synthetic gas condensate.Methanol, propanol and methylene chloride are the solvents used to remove the condensate banking and improve the gas effective permeability near to the wellbore. Solvents are injected in Berea sandstone rock with similar petrophysical properties in order to compare the efficiency at removing the condensate banking. It was observed that all of the solvents improved the gas effective permeability after removing banking condensate; however, methanol was the more efficient solvent to remove it while methylene chloride had the lowest values of gas effective permeability after removing the banking condensate.